SAME-SEX MARRIAGE IN THE BRAZILIAN SUPREME COURT: Legal Reasoning and the Risk of a Regressive Turn - PÜSCHEL,FLAVIA PORTELLA (2019)
ABSTRACT This paper investigates how far the Brazilian Supreme Court has argumentatively committed itself to upholding same-sex marriage in the face of prospective restrictive legislation based on the reasoning the court used in its 2011 ruling about same-sex domestic partnerships. The paper concludes that the separation of litigation over domestic partnerships and marriage may have led to the risk of a regressive turn concerning gay rights on this matter.